Calanus spp. and Metridia spp. size and lipid content metrics in the Northwest Atlantic, 1977-2020 - Laura K Helenius; Erica J H Head; Phoebe Jekielek; Christopher D Orphanides; Pierre Pepin; Geneviève Perrin; Stéphane Plourde; Marc Ringuette; Jeffrey A Runge; Harvey Joseph Walsh; Catherine L Johnson (PANGAEA, 2024)
Measurements of body size (prosome length), dry weight, and lipid content (oil sac area and volume) in wild-caught copepods were compiled from multiple studies conducted in the northwest Atlantic between 1977 and 2020, across all months of the year. The merged dataset includes data from >150 field missions and time series stations sampled by Fisheries and Oceans Canada, National Oceanic and Atmospheric Administration, and academic institutions, with spatial coverage from the Gulf of Maine, Georges Bank, Nantucket Shoals, Scotian Shelf, Gulf of St. Lawrence, Labrador Sea, and the Newfoundland Shelf. The copepod species included in the data set are Calanus spp. (C. hyperboreus, C. glacialis, C. finmarchicus) and Metridia longa. Wild-collected copepods were sampled using a variety of plankton nets, as described in the metadata for each data point. This amalgamated historical dataset provides a large-scale perspective on copepod size and lipids across a large geographic and temporal range.